2002
DOI: 10.1080/gye.16.4.331.334
|View full text |Cite
|
Sign up to set email alerts
|

Turner's syndrome followed by acromegaly in the third decade of life: an unusual coincidence of two rare conditions

Abstract: We present an unusual coincidence of acromegaly and Turner's syndrome. A girl was diagnosed with Turner's syndrome when she presented with short stature, primary amenorrhea, Hashimoto's thyroiditis, and some heart and renal anomalies. No therapy with growth hormone and only a few months treatment with estrogen-progestin was given. A typical picture of acromegaly occurred in the third decade of her life. Bone radiographs and densitometry suggested the more pronounced influence of acromegaly within the skeleton,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Pituitary adenomas have also rarely been identified in TS patients. Review of the literature demonstrated nine case reports of women with TS who presented with pituitary adenomas during late adolescence or adulthood; six were diagnosed with functioning pituitary adenoma and three with non-functioning pituitary adenoma as in our case [8,[18][19][20][21][22][23][24][25] (Table 2). Non-functioning pituitary adenomas in children and adolescents are rare; they comprise only 4 to 6% of pediatric patients, while they account for approximately 33 to 50% of adult patients with pituitary lesions [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary adenomas have also rarely been identified in TS patients. Review of the literature demonstrated nine case reports of women with TS who presented with pituitary adenomas during late adolescence or adulthood; six were diagnosed with functioning pituitary adenoma and three with non-functioning pituitary adenoma as in our case [8,[18][19][20][21][22][23][24][25] (Table 2). Non-functioning pituitary adenomas in children and adolescents are rare; they comprise only 4 to 6% of pediatric patients, while they account for approximately 33 to 50% of adult patients with pituitary lesions [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of Turner syndrome accompanied by pituitary adenomas are very rare. The search of the MEDLINE database retrieved only two cases of Turner syndrome accompanied by acromegaly 4,5 . The association of Turner syndrome with pituitary hyperplasia verified by histological examination, unfortunately at autopsy, was published in one case 6 , with nonfunctioning pituitary microadenoma in two cases 7,8 , while in two more casesthe presence of prolactinoma was demonstrated 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of the short stature homeobox‐containing gene (SHOX) on the short arm of the X and Y chromosomes have been described in short children with Turner and Leri‐Weill syndromes and/or congenital heart defects (22). The reported case of adult acromegaly in a patient of short stature with Turner syndrome and congenital cardiac defects (23) may provide another link between growth hormone and the heart. Finally, at least eight disease gene mutations have been described in patients with cardiomyopathy, many of whom have short stature.…”
mentioning
confidence: 99%